Ownership Structures and Dividend Policy: Evidence from Listed Construction Companies in Poland - Andrzej ZYGULA (Communications of International Proceedings, 2021)
The aim of the article is to present the results of the research on the influence of the ownership structure on the dividend decisions of the companies. The research was conducted on the companies listed on the main market of the Warsaw Stock Exchange (WIG-construction). The data was obtained from the Notoria Serwice database. The research was carried out using the logit regression method. The research results showed that the influence of foreign ownership and / or corporate ownership on dividend payments is statistically significant and negative. Moreover, it was also shown that the influence of financial ownership on dividend payments is statistically significant and positive.
Keywords: Ownership; Agency Problem; Dividend Policy; Dividends